2013
DOI: 10.1155/2013/625767
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Carbon Stock and Plant Biodiversity in Collaborative Forests in Terai, Nepal

Abstract: Reducing emission from deforestation and forest degradation (REDD+) programme has prime concern to carbon stock enhancement rather than biodiversity conservation. Participatory managed forest has been preparing to get benefit under this programme, and collaborative forest is one of them in Nepal. Hence, this research is intended to assess the relationship between carbon stock and biodiversity. Three collaborative forests (CFMs) were selected as study sites in Mahottari district, Nepal. Altogether 96 sample plo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 6 publications
3
21
2
3
Order By: Relevance
“…The unimodal associations between AGC and tree species evenness in montane forests and for small tree sizes in miombo woodlands (Table 2; Fig. 3), is different from previous studies from sub-tropical forests in Puerto Rico (Vance-Chalcraft et al 2010) and in the Terai area of Nepal (Mandal, Dutta, Jha, & Karmacharya 2013). This discrepancy could be due to differences in forest tree structure response to growth limiting factors, such as light availability (Cai, Poorter, Han, & Bongers 2008).…”
Section: Variablescontrasting
confidence: 56%
“…The unimodal associations between AGC and tree species evenness in montane forests and for small tree sizes in miombo woodlands (Table 2; Fig. 3), is different from previous studies from sub-tropical forests in Puerto Rico (Vance-Chalcraft et al 2010) and in the Terai area of Nepal (Mandal, Dutta, Jha, & Karmacharya 2013). This discrepancy could be due to differences in forest tree structure response to growth limiting factors, such as light availability (Cai, Poorter, Han, & Bongers 2008).…”
Section: Variablescontrasting
confidence: 56%
“…In some cases, lower carbon stocks can exist even in highly diverse forests if the dominant tree species has a low carbon storage capacity (Kirby & Potvin 2007;Baral et al 2009). Mandal et al (2013) and Kimaro and Lulandala (2013) found negative relationships between carbon and plant species diversity. Forest thinning through selective removal of large trees may reduce carbon without impacting negatively on plant species diversity (Widenfalk & Weslien 2009), and the majority of CFs in our study apply thinning to extract large trees.…”
Section: Carbon Plant Diversity Attributes and Forest Products Corrementioning
confidence: 99%
“…Variasi karbon tersimpan tidak berpengaruh dengan biodiversitas tanaman. Hasil ini sejalan dengan hasil penelitian Mandal et al (2013) dan Karna (2012).…”
Section: Korelasi Indeks Biodiversitas Tanaman Dan Karbon Tersimpanunclassified